Events and Causes Between Copts and Muslims During the Reign of Sultan An-Nasır Muhammad (721/1321 Events) - Eser, Mehmet Emin (Kahramanmaraş Sütçü İmam Üniversitesi, 2024)
This article focuses on a series of events examining the relationships between Muslim and dhimmi communities in 14th century Egypt. During the third reign of Sultan Nasir Muhammad (709-741/1309-1341), Jews and Christians faced specific restrictions and challenges. Decrees such as the conversion of some churches into mosques and the prohibition of the Feast of the Martyrs (celebrated on the eighth day of Bishan month) were issued during this period. However, it is observed that these prohibitions were gradually forgotten over time. In some incidents, examples were found where dhimmis were punished as a result of disagreements with Muslims. Positive developments for dhimmis also occurred during Sultan Nasir Muhammad's reign, such as the establishment of diplomatic relations with European states and the opening or reconstruction of churches in the country. However, negative events for dhimmis were also recorded, particularly issues related to the extradition of prisoners with envoys from neighboring countries. In conclusion, it is evident that certain events during this period increased tension between Muslim and dhimmi communities. Examining Sultan Nasir Muhammad's tolerant approach towards them and the analysis of diplomatic relations with neighboring countries contribute to a better understanding of this era.

Bu makale, XIV. yy. Mısır’ında Müslüman ve zimmî topluluklar arasındaki ilişkileri inceleyen bir dizi olaya odaklanmıştır. Sultan Nasır Muhammed’in üçüncü saltanat dönemi (709-741/1309-1341) olan bu zaman diliminde, Yahudiler ve Hristiyanlar, belirli kısıtlamalara ve zorluklara maruz kalmışlardır. Bazı kiliselerin camilere dönüştürülmesi ve özellikle Şehitler Bayramı’nın (Başan ayının sekizi) yasaklanması gibi kararnameler bu dönemde yayınlanmıştır. Ancak bu yasaklamaların zamanla unutulduğu görülmüştür. Bazı olaylarda, Müslümanlarla yaşadıkları anlaşmazlıklar sonucunda zimmîlerin cezalandırıldığına dair örneklere rastlanmıştır. Sultan Nasır Muhammed Dönemi boyunca zimmîler için bazı olumlu gelişmeler de yaşanmıştır. Avrupa devletleriyle diplomatik ilişkilerin kurulması, ülkede kiliselerin açılması veya yeniden inşa edilmesi bu olaylara örnektir. Ancak zimmîler için bazı olumsuz olaylar da kaydedilmiştir. Özellikle komşu ülkelerden gelen elçilerle esir iadesi konusunda yaşanan sorunlar bunlardan bazılarıdır. Sonuç olarak, bu dönemde Müslüman ve zimmî topluluklar arasında meydana gelen bazı olayların aralarındaki gerginliği arttırdığı görülmüştür. Sultan Nasır Muhammed’in onlara yönelik hoşgörülü tutumu ve komşu ülkelerle diplomatik ilişkilerin incelenmesi bu dönemin daha iyi anlaşılmasına katkı sağlamaktadır.
Sultan en-Nasır Muhammed Döneminde Kıptîler ile Müslümanlar Arasındaki Olaylar ve Nedenleri (721/1321 Olayları)
Keywords: Islamic Studies (Other); İslam Araştırmaları (Diğer)